2022
DOI: 10.1177/01492063221121787
|View full text |Cite
|
Sign up to set email alerts
|

Visible but Hidden: An Intersectional Examination of Identity Management Among Sexual Minority Employees

Abstract: As organizations have increasingly prioritized the inclusion of sexual minorities, there has been a proliferation of studies examining the ways by which organizations can foster environments that enable sexual minorities to express themselves authentically at work. Yet, extant research has predominantly ignored the role of other social identities in shaping the experiences of sexual minority employees, their decisions regarding the ways they express their sexual identities at work, and the consequences of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 68 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Studies in this issue highlight a range of invisible inequalities that can be experienced due to attributes or characteristics that are not readily apparent. These include social class (Côté, 2023;Meuris & Gladstone, 2023), caste (Majumder & Arora, 2023), neurodiversity (Ezerins et al, 2023), mental illness (Colella & Santuzzi, 2022), and sexual orientation (Dhanani, Totton, Hall, & Pham, 2022;Roberson, Ruggs, Pichler, & Holmes, 2023).…”
Section: Examples Of Invisible Inequalities and Their Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies in this issue highlight a range of invisible inequalities that can be experienced due to attributes or characteristics that are not readily apparent. These include social class (Côté, 2023;Meuris & Gladstone, 2023), caste (Majumder & Arora, 2023), neurodiversity (Ezerins et al, 2023), mental illness (Colella & Santuzzi, 2022), and sexual orientation (Dhanani, Totton, Hall, & Pham, 2022;Roberson, Ruggs, Pichler, & Holmes, 2023).…”
Section: Examples Of Invisible Inequalities and Their Implicationsmentioning
confidence: 99%
“…For example, as Colella and Santuzzi (2022) outlined, while concealing mental illnesses might protect individuals from discrimination, it may subject them to inequalities such as misattribution of performance shortfalls to competence rather than illness. Highlighting identity management implications that are linked to concealment or revealment, Dhanani et al (2022) found that White people who experience racial and heterosexist harassment conceal their sexual orientation and suppress their racial identity. These authors found further that such concealment and suppression decrease employee well-being.…”
Section: Examples Of Invisible Inequalities and Their Implicationsmentioning
confidence: 99%
See 3 more Smart Citations